Altered Thymic Function during Interferon Therapy in HCV-Infected Patients - Beq, Stephanie; Rozlan, Sandra; Pelletier, Sandy; Willems, Bernard; Bruneau, Julie; Lelievre, Jean-Daniel; Levy, Yves; Shoukry, Naglaa H.; Cheynier, Rémi (PLOS ONE, 2012)
Interferon alpha (IFNα) therapy, despite good efficacy in curing HCV infection, leads to major side effects, in particular inducement of a strong peripheral T-cell lymphocytopenia. We here analyze the early consequences of IFNα therapy on both thymic function and peripheral T-cell homeostasis in patients in the acute or chronic phase of HCV-infection as well as in HIV/HCV co-infected patients. The evolution of T-cell subsets and T-cell homeostasis were estimated by flow cytometry while thymic function was measured through quantification of T-cell receptor excision circles (TREC) and estimation of intrathymic precursor T-cell proliferation during the first four months following the initiation of IFNα therapy. Beginning with the first month of therapy, a profound lymphocytopenia was observed for all T-cell subsets, including naïve T-cells and recent thymic emigrants (RTE), associated with inhibition of intrathymic precursor T-cell proliferation. Interleukin (IL)-7 plasma concentration rapidly dropped while lymphocytopenia progressed. This was neither a consequence of higher consumption of the cytokine nor due to its neutralization by soluble CD127. Decrease in IL-7 plasma concentration under IFNα therapy correlated with the decline in HCV viral load, thymic activity and RTE concentration in blood. These data demonstrate that IFNα-based therapy rapidly impacts on thymopoiesis and, consequently, perturbs T-cell homeostasis. Such a side effect might be detrimental for the continuation of IFNα therapy and may lead to an increased level of infectious risk, in particular in HIV/HCV co-infected patients. Altogether, this study suggests the therapeutic potential of IL-7 in the maintenance of peripheral T-cell homeostasis in IFNα-treated patients.